STRATEGI PEMASARAN BERBASIS BUDAYA DAN SYARIAH: PENGGUNAAN SIMBOL JAWA DALAM BRANDING PRODUK MUSLIM: Culture and Sharia-Based Marketing Strategies: The Use of Javanese Symbols in Muslim Product Branding - Saripermanik Budayanti (tesco publisher, 2025)
This study aims to explore the effectiveness of marketing strategies that integrate Javanese cultural visual identity with sharia principles in the Muslim product industry, particularly batik. Amidst the currents of globalization and the dominance of Middle Eastern Islamic symbolism, there is an urgency to understand how local wisdom can synergize with halal labels to attract local consumers. This study uses a qualitative case study approach in batik industry centers in Central Java. Data were collected through in-depth interviews, participant observation of branding materials, and document analysis. The results show that: (1) The combination of Javanese symbols (such as Gunungan, Kawung motifs) with calligraphy or halal labels creates a perception of